The shifting sands of space security: The Politics and Law of The Peaceful Uses of Outer Space - Blount, P J (UI Scholars Hub, 2019)
This article argues that the content of the legal term “peaceful purposes,”as used in international space law is changing. Peaceful Purposes as understood throughout the bulk of the Space Age has encompassed not only the UN Charter’s prohibitions on the use of force, but also a number of customary international law principles that enhanced it beyond mere non-aggression. Through an examination of state practice with regards to the military uses of outer space, this article concludes that the legal content of peaceful purposes is eroding towards an alignment with “non-aggressive” as understood in the law concerning the use of force. Specifically, this article argues that geopolitical and technological changes are encouraging states to pursue disruption in the space environment rather than stability, and this has been matched with state practice and rhetoric that exhibits that states are moving toward more offensive, rather than defensive, stances in the space environment.